VERBAL REPRESENTATION OF CULTURAL CODES IN ADVERTISING: A COMPARATIVE STUDY OF ENGLISH AND UZBEK LANGUAGES (Eureka Journal of Language, Culture & Social Change, 2026)
This study examines the verbal representation of cultural codes in advertising discourse in English and Uzbek languages. Advertising language reflects cultural values through idioms, metaphors, and fixed expressions. The research identifies that English advertisements mainly emphasize individuality, freedom, and innovation, while Uzbek advertisements highlight collectivism, family values, and tradition. The comparative analysis shows how linguistic strategies are shaped by cultural differences in persuasive communication.
Keywords: Advertising discourse, cultural codes, verbal representation, comparative linguistics, English, Uzb.